1995
DOI: 10.1155/1996/46596
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Irrigation With MagneticallyTreated Water on The Translocation ofMinerals in The Soil

Abstract: Magnetically treated water (MTW) is water passed through a magnetic field before being used. Applications of MTW are abundant in industry where it is used to prevent scaling on inner walls of pipes conveying fluids, especially water. In recent years scientists investigating the subject have concluded that the magnetic field interacts with the surface charges of particles in the fluid solutions affecting the crystallisation and precipitation of the solids in them. These processes are of significant effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 1 publication
(1 reference statement)
3
31
0
1
Order By: Relevance
“…He pointed that magnetic water could stimulate the defence system of plants, photosynthetic activity and translocation efficiency of photoassimilates. Noran et al (1996) also confirmed the assumption that as a result of the influence of the magnetic field on solutes, the interaction between soil particles and salts dissolved in ordinary water did not resemble the interaction between the soil particles and the salts dissolved in magnetically treated water. Muraji et al (1998) discovered that there was an enhancement in root growth of maize (Zea mays) by exposing the maize seedling to 50 G magnetic fields at alternating frequencies of 40-160 Hz.…”
Section: Introductionsupporting
confidence: 78%
“…He pointed that magnetic water could stimulate the defence system of plants, photosynthetic activity and translocation efficiency of photoassimilates. Noran et al (1996) also confirmed the assumption that as a result of the influence of the magnetic field on solutes, the interaction between soil particles and salts dissolved in ordinary water did not resemble the interaction between the soil particles and the salts dissolved in magnetically treated water. Muraji et al (1998) discovered that there was an enhancement in root growth of maize (Zea mays) by exposing the maize seedling to 50 G magnetic fields at alternating frequencies of 40-160 Hz.…”
Section: Introductionsupporting
confidence: 78%
“…68.5 and 362.5 ppm (at march) to 32.3,43.3 and 246.8 ppm (in July) for N,P and K respectively. Noran et al 1996 andGrewal,2009 mentioned that plants absorb more water of MTW than non-treated, consequently they uptake more nutrients as a result of water molecules of MTW are minute and small and is reflected on the yield and water productivity. These results clear that MTW have played important role in improving the availability of these elements to plants.…”
Section: Available Nutrients In Soilmentioning
confidence: 99%
“…A pesar de estos últimos resultados, no existe una teoría completa y uniforme que explique los efectos del ATM en el metabolismo de las plantas. Sin embargo, no es improbable que estos efectos sean indirectos, es decir, a través de una modificación del perfil de humedad del suelo o un mejoramiento de la disponibilidad de nutrientes alrededor de las raíces, como sugieren algunos trabajos (Khoshravesh, Mostafazadeh-Fard, Mousavi, & Kiani, 2011;Maheshwari & Grewal, 2009;Noran, Shani, & Lin, 1996). Más aún, estudios biológicos in vivo han demostrado que la permeabilidad de los canales de iones en las membranas y en las células aumenta, involucrando también la actividad de los iones de calcio y el equilibrio de las concentraciones de iones (Smith, McLeod, Liboff, & Cooksey, 1987).…”
Section: Introductionunclassified